AFR100 donor visit to Olokemeji Reforestation site - International Institute of Tropical Agriculture (IITA, 2023)
IITA Forest Center emerged as one of the Top 100 cohort members of TerraFund for AFR100 in the framework of accelerating the implementation of the African Forest Landscape Restoration Initiative (AFR100) aiming to restore 100 million hectares of deforested and degraded lands across Africa by 2030. Recently, five representatives of the TerraFund for AFR100 team visited the reforestation site in Olokemeji, Ogun State, Nigeria to assess the progress of the project. Of the 5800 hectares of Olokemeji Forest reserve, IITA Forest Center is currently reforesting about 918 hectares, with 22 native species consisting of fruit and timber trees. This video documents their reaction to the progress of the project.